Ethanol Production from Oil Palm Trunk: A Combined Strategy Using an Effective Pretreatment and Simultaneous Saccharification and Cofermentation - Agustin Krisna Wardani; Aji Sutrisno; Titik Nur Faida; Retno Dwi Yustina; Untung Murdiyatmo (International Journal of Microbiology)
Background. Oil palm trunk (OPT) with highly cellulose content is a valuable bioresource for bioethanol production. To produce ethanol from biomass, pretreatment is an essential step in the conversion of lignocellulosic biomass to fermentable sugars such as glucose and xylose. Several pretreatment methods have been developed to overcome biomass recalcitrance. In this study, the effects of different pretreatment methods such as alkali pretreatment, microwave-alkali, and alkaline peroxide combined with autoclave on the lignocellulosic biomass structure were investigated. Moreover, ethanol production from the treated biomass was performed by simultaneous saccharification and cofermentation (SSCF) under different temperatures, fermentation times, and cell ratios of Saccharomyces cerevisiae NCYC 479 and pentose-utilizing yeast, Pichia stipitis NCYC 1541. Results. Pretreatment resulted in a significant lignin removal up to 83.26% and cellulose released up to 80.74% in treated OPT by alkaline peroxide combined with autoclave method. Enzymatic hydrolysis of treated OPT resulted in an increase in fermentable sugar up to 93.22%. Optimization of SSCF by response surface method showed that the coculture could work together to produce maximum ethanol (1.89%) and fermentation efficiency (66.14%) under the optimized condition. Conclusion. Pretreatment by alkaline peroxide combined with autoclave method and SSCF process could be expected as a promising system for ethanol production from oil palm trunk and various lignocellulosic biomass.